Integrating human factors in the design of intelligent systems: an example in air traffic control. (27th May 2009) - Debernard, Serge; Guiost, Benoit; Poulain, Thierry; Crevits, Igor; Annebicque, David; Millot, Patrick
In the current organisation of air traffic control, some cooperative activities appear in the work of air traffic controllers, especially between Tactical Controllers (TC) and Planning Controllers (PC), who manage aircraft inside a sector to prevent collisions. These cooperative activities allow building and maintaining a Common Frame of References (COFOR) to be built and maintained. The COFOR is an internal representation of the situation, and introducing specific assistance based on this COFOR not only improves the effectiveness of the human activities, but also improves the controller's situation awareness and the human-machine cooperation. This article presents a study of a project called Automation and MAN-machine Delegation of Action (AMANDA), which proposes assistance to the controllers for resolving aerial conflict. In order to avoid decisional conflict between human operators and the assistance system, AMANDA integrates human strategies for calculating new trajectories that which avoid conflicts and communicates with controllers through a Common Work Space (CWS), which is a physical representation of the human operators' COFORs. This study took place in three steps. The first step, based on an experimental investigation, allowed the content of the COFOR to be defined. In the second step, the CWS supporting human-human and human-machine cooperation and the characteristics of the support tool were defined. In the last one, the proposed principles were evaluated by professional air traffic controllers.